2002
DOI: 10.1145/503124.503125
|View full text |Cite
|
Sign up to set email alerts
|

Who is an open source software developer?

Abstract: Profiling a community of Linux developers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 2 publications
3
33
0
Order By: Relevance
“…In GitHub, a set of commits could be grouped together as a release being a phase achievement of the project 3 . Here we simply define a release r j as a set of commits (the number of commits is |r j |).…”
Section: Independent Variables (Ivs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In GitHub, a set of commits could be grouped together as a release being a phase achievement of the project 3 . Here we simply define a release r j as a set of commits (the number of commits is |r j |).…”
Section: Independent Variables (Ivs)mentioning
confidence: 99%
“…They joined an OSS project with different motivations [1,2]. Consequently, the degree of their participation and the level of their contributions are diversified [3]. A set of individualized characteristics on the behaviors of OSS developers that distinguish one from others who belong to the same OSS project team do indeed exist [4].…”
Section: Introductionmentioning
confidence: 99%
“…Dempsey et al [6] analyzed the top-level domain name of the email address (e.g., .ca, .com) of the participant to identify the country of the participant. However the study did not compensate for the US bias resulting from the wide use of generic domains (e.g., .com).…”
Section: Related Workmentioning
confidence: 99%
“…Prior work (e.g., [6], [8]) primarily used the toplevel domain name of an email address to identify a participant's country. Such work can identify a limited number of participants since many participants use email addresses that are not specific to any country, such as "hotmail.com".…”
Section: Identifying the Country Of A Participantmentioning
confidence: 99%
“…There is some evidence that in FOSS this fourth group of participants may be particularly important. For example, two studies of larger FOSS projects, Linux (Dempsey, et al, 2002) and the GNOME desktop environment (Koch and Schneider, 2002), found that a smaller set of "core" developers contributed a majority of the code to these projects [15].…”
Section: The Negative Effects Of Institutions?mentioning
confidence: 99%